Environment-friendly corrosion-resistant thermoplastic elastomer sealing material and preparation method thereof
By adopting the preparation method of environmentally friendly corrosion-resistant thermoplastic elastomer sealing materials, using recycled rubber powder and low-cost mineral fillers, combined with dynamic vulcanization blending and secondary crosslinking reaction, the problems of low production efficiency and high cost of existing fluoroelastic sealing materials are solved, performance improvement and cost reduction are achieved, and sealing needs of high-end semiconductor equipment are met.
Patent Information
- Application Number
- CN202411714178.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing fluoroelastic sealing materials are inefficient and cannot meet the requirements of sealing high-end semiconductor equipment. At the same time, the cost is high, which restricts the development of the semiconductor industry.
The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material is made of plastic, raw glue, recycled glue powder, acid absorbent, filler, vulcanization system compounding agent, antioxidant and other additives. It is prepared by high-temperature activation of recycled glue powder, plasticized raw glue, uniform refining, dynamic vulcanization blending and secondary crosslinking reactions to prepare sealing materials with excellent performance.
The performance improvement of sealing materials has been achieved, including Mooney viscosity, low-temperature brittleness, tensile strength, tensile elongation, oil resistance and aging resistance, etc., and the cost is reduced by 20% to 30%, meeting the sealing needs of high-end semiconductor equipment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of special sealing manufacturing of semiconductor equipment, and in particular to an environmentally friendly corrosion-resistant thermoplastic elastomer sealing material and a preparation method thereof. Background Art
[0002] Semiconductor equipment is a precision instrument. Due to its special use environment, seals for semiconductor equipment need to have good sealing, chemical corrosion resistance and ductility. The semiconductor manufacturing process involves many wet processes, and a variety of chemicals are used in the wet process of semiconductor manufacturing, including strong acids, alkalis, oxidants and corrosive solvents. Therefore, the semiconductor processing and manufacturing process has strict requirements on the chemical compatibility and purity of component materials, especially sealing materials. Special rubber materials are usually the first choice, especially fluororubber.
[0003] At present, the preparation method of fluororubber sealing materials in China is inefficient and the product performance cannot meet the sealing requirements of high-end semiconductor equipment. At the same time, the cost of fluororubber is relatively high, which makes the cost of the semiconductor industry remain high and restricts its development. Summary of the invention
[0004] The object of the present invention is to provide an environmentally friendly corrosion-resistant thermoplastic elastomer sealing material with excellent performance and low cost.
[0005] The purpose of the present invention is to provide a method for preparing an environmentally friendly corrosion-resistant thermoplastic elastomer sealing material, which can be industrially produced.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] In one aspect, the present invention provides an environmentally friendly corrosion-resistant thermoplastic elastomer sealing material, which is made of the following raw materials in parts by weight:
[0008] 1 to 6 pieces of plastic;
[0009] 50-65 parts of raw rubber;
[0010] 5-30 parts of recycled rubber powder;
[0011] 1 to 6 parts of acid absorbent;
[0012] 6-20 parts of filler;
[0013] Vulcanization system ingredients: 1-3 parts of vulcanizing agent, 0.2-1.5 parts of accelerator;
[0014] 1 to 6 parts of antioxidant;
[0015] Other additives 0-5 parts.
[0016] Preferably, the plastic is polytetrafluoroethylene particles of 120-200 mesh.
[0017] Preferably, the raw rubber is a special rubber, preferably fluororubber, silicone rubber or hydrogenated nitrile.
[0018] Preferably, the reclaimed rubber powder is special rubber waste rubber powder or special rubber reclaimed rubber powder, and the mesh number is ≥100 meshes.
[0019] Preferably, the acid absorber is one or more of magnesium oxide (MgO), calcium hydroxide (Ca(OH)2), zinc oxide (ZnO), and calcium carbonate (CaCO3).
[0020] Preferably, the vulcanization system is a bisphenol vulcanization system: bisphenol AF + benzyltriphenylphosphine chloride (BPP) vulcanization system or a peroxide vulcanization system: such as diisopropyl peroxide (DCP) + dibenzothiazole disulfide (DM) peroxide vulcanization system or an amine vulcanization system: such as ammonium thiocyanate + cobalt-sulfur accelerator and other non-sulfur vulcanization systems.
[0021] Preferably, the filler is a mineral material, more preferably clay, bentonite, kaolin and the like.
[0022] Preferably, the antioxidant is ferric oxide.
[0023] Different types of special rubbers can be added with other additives according to the requirements of material properties, such as hydroxy silicone oil, sodium stearate, phenolic resin, amino resin, etc.
[0024] On the other hand, the present invention also provides a method for preparing the above-mentioned environmentally friendly corrosion-resistant thermoplastic elastomer sealing material, comprising the following steps:
[0025] Step 1) Activating the regenerated rubber powder at high temperature, the activation temperature is 200° C., and the activation time is 30 to 50 minutes;
[0026] Step 2) The raw rubber is plasticized at room temperature for 5 to 10 minutes to obtain plasticized rubber, and then the activated recycled rubber powder, filler, plastic and plasticized rubber are mixed and kneaded evenly in a kneader or an internal mixer at 160±5°C to obtain mixed plastic, and the mixing time is 10 to 15 minutes; then a vulcanization system compounding agent, an acid absorber, an antioxidant and other additives are added to disperse them evenly;
[0027] Step 3) placing the synthesized plastic into a twin-screw extruder at 180-200° C., and performing continuous crosslinking reaction by means of dynamic vulcanization blending and strong mechanical shear stress, with a crosslinking time of 20-40 minutes;
[0028] Step 4) performing a secondary cross-linking reaction at 200-220° C. for 6-8 hours.
[0029] Furthermore, before the secondary cross-linking reaction, the material obtained by the primary cross-linking reaction is molded at 180-200° C. for 20-40 minutes to form a sheet.
[0030] The recycled rubber powder used in the present invention is made from waste rubber, has a cost of only 1 / 10 of that of raw rubber, is easier to disperse evenly than blocky raw rubber and plastic, and has greatly improved performance; the reinforcing material used is a low-cost mineral material; by comparison, the mechanical properties, aging resistance and compression deformation of the material added with the recycled rubber powder are all improved, and the air permeability coefficient is basically the same, so using the recycled rubber powder directly to prepare the thermoplastic elastomer RPTPE is a new way to energy-saving, environmentally friendly and recycling special waste rubber.
[0031] Compared with the prior art, the Mooney viscosity of the RPTPE prepared by the present invention is 35-59 (ML1+10, 121°C), the low temperature brittleness is -18--73°C (largely related to the type of raw rubber), the tensile strength is 8.9-12MPa, the elongation at break is 268.6%-292%, the Shore hardness is 76-86, and its physical properties are compression permanent deformation of 2.8-13.8%, and the air permeability coefficient / cm 2 .s -1 .pa -1 4.27×10 -14 ~7.13×10 -14 ;
[0032] 200℃, 72h test of its thermal oxidation aging properties: hardness change -1~0, tensile strength change rate -3.9~-1.5%, elongation at break change rate -9.87~-0.4%, high temperature permanent compression deformation 34.4~51.21%;
[0033] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 0-0.3%, the Shore hardness changes from -5 to -2, and the volume change rate is +0.02% to +0.76%;
[0034] The product performance meets the requirements of GB / T 528-2009, Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, GB / T 531-2008, Determination of low-temperature brittleness of vulcanized rubber or thermoplastic rubber (multiple specimen method), GB / T 5720-2008, Test method for O-ring of rubber seals, GB / T 7759-2015, Determination of compression permanent deformation of vulcanized rubber or thermoplastic rubber, etc. Compared with DuPont's fluorosilicone material LS5043H, the tensile strength, oil resistance and aging resistance are significantly improved, while the cost is reduced by 20% to 30%. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below with reference to specific embodiments.
[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0037] The terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range are also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope. Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art of the present invention. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] The normal temperature in the embodiment of the present invention refers to 25±2°C.
[0041] The parts of the present invention, unless otherwise specified, refer to the parts by mass.
[0042] The raw materials of the embodiments of the present invention can all be purchased.
[0043] Example 1
[0044] Step 1) activating 10 kg of fluororubber reclaimed rubber powder (200 mesh) at 200° C. for 30 min;
[0045] Step 2) 25 kg of fluororubber raw rubber was plasticized for 5 minutes at room temperature to obtain plasticized rubber, and then the activated 200-mesh fine fluororubber recycled rubber powder, 7.5 kg of clay and 1.5 kg of powdered 100-mesh polytetrafluoroethylene were evenly dispersed in an internal mixer to obtain a mixture, and the mixture was added to the plasticized rubber at 160±5° C. and mixed evenly to obtain mixed plastic, and the mixing time was 15 minutes; then a bisphenol vulcanization system (0.5 kg of bisphenol AF, 0.125 kg of BPP), 1.5 kg of calcium hydroxide, 0.75 kg of magnesium oxide, and 0.75 kg of ferric oxide were added and dispersed evenly;
[0046] Step 3) adding the plastic mixture into a twin-screw extruder at 190° C. to perform continuous crosslinking reaction by means of dynamic vulcanization blending and strong mechanical shear stress, and the crosslinking time is 20 minutes;
[0047] Step 4) The above material is molded into a sheet at 190° C. for 30 minutes, and a secondary cross-linking reaction is carried out at 200° C. for 6 hours to obtain a high-quality thermoplastic elastomer sealing material.
[0048] Performance testing of the product: Performance testing was carried out according to JF01-58-2019. The Mooney viscosity of the prepared special sealing material was 59 (ML1+10, 121°C), low-temperature brittleness was -18°C, tensile strength was 10.3MPa, elongation at break was 268.6%, Shore hardness was 85, and its physical properties compression permanent deformation was 13.8%. Air permeability coefficient / cm 2 .s -1 .pa -1 is 6.77×10 -14 ;
[0049] 200℃, 72h test of its thermal oxidation aging properties: hardness change -1, tensile strength change rate -3.2%, elongation at break change rate -1.3%, high temperature permanent compression deformation 50.8%;
[0050] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 0.06%, the Shore hardness change is -3, and the volume change rate is +0.45%;
[0051] Example 2
[0052] Step 1) activating 5 kg of fluororubber reclaimed rubber powder (200 mesh) at 200° C. for 30 min;
[0053] Step 2) 25 kg of fluororubber raw rubber was plasticized at room temperature for 5 min to obtain plasticized rubber, and then the activated 200-mesh fine fluororubber recycled rubber powder, 2.5 kg of clay and 1.5 kg of powdered 100-mesh polytetrafluoroethylene were evenly dispersed in an internal mixer to obtain a mixture, and the mixture was added to the plasticized rubber at 160±5°C and mixed evenly to obtain mixed plastic, with a mixing time of 15 min; then a bisphenol vulcanization system (0.375 kg of bisphenol AF, 0.125 kg of BPP), 1.5 kg of calcium hydroxide, 0.75 kg of magnesium oxide, and 0.75 kg of ferric oxide were added and dispersed evenly.
[0054] Step 3) Add the synthesized plastic mixture into a twin-screw extruder at 190° C., and perform continuous crosslinking reaction by means of dynamic vulcanization blending and strong mechanical shear stress, and the crosslinking time is 35 minutes.
[0055] Step 4) The above material is molded into a sheet at 190° C. for 35 minutes, and a secondary cross-linking reaction is carried out at 200° C. for 6 hours to obtain a high-quality thermoplastic elastomer sealing material.
[0056] Performance testing of the product: Performance testing was carried out according to JF01-58-2019. The Mooney viscosity of the prepared special sealing material is 41 (ML1+10, 121°C), low-temperature brittleness is -22°C, tensile strength is 9MPa, elongation at break is 292%, Shore hardness is 80, and its physical properties are compression permanent deformation of 3.3%. Air permeability coefficient / cm2.s -1 .pa -1 7.13×10 -14 ;
[0057] 200℃, 72h test of its thermal oxidation aging properties: hardness change 0, tensile strength change rate -1.5%, elongation at break change rate -6.59%, high temperature permanent compression deformation 38.5%;
[0058] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 0.2%, the Shore hardness changes by -2, and the volume change rate is +0.02%;
[0059] Example 3
[0060] Step 1) activating 7.5 kg of fluororubber reclaimed rubber powder (200 mesh) at 200° C. for 40 min;
[0061] Step 2) 25 kg of fluororubber raw rubber is plasticized at room temperature for 5 min to obtain plasticized rubber, and then the activated 200-mesh fine fluororubber recycled rubber powder, 5 kg of clay and 1.5 kg of powdered 100-mesh polytetrafluoroethylene are evenly dispersed in an internal mixer to obtain a mixture, and the mixture is added to the plasticized rubber at 160±5°C and mixed evenly to obtain mixed plastic, with the mixing time being 15 min; then a bisphenol vulcanization system (0.5 kg of bisphenol AF, 0.125 kg of BPP), 1.5 kg of calcium hydroxide, 0.75 kg of magnesium oxide, and 0.75 kg of ferric oxide are added and dispersed evenly.
[0062] Step 3) Add the synthesized plastic mixture into a twin-screw extruder at 190° C., and perform continuous crosslinking reaction by means of dynamic vulcanization blending and strong mechanical shear stress, and the crosslinking time is 25 minutes.
[0063] Step 4) The above material is molded into a sheet at 190° C. for 25 minutes, and a secondary cross-linking reaction is carried out at 220° C. for 8 hours to obtain a high-quality thermoplastic elastomer sealing material.
[0064] Performance testing of the product: Performance testing was carried out according to JF01-58-2019. The Mooney viscosity of the prepared special sealing material was 48 (ML1+10, 121°C), low temperature brittleness was -20°C, tensile strength was 10.3MPa, elongation at break was 276.5%, Shore hardness was 83, and its physical properties compression permanent deformation was 7.4%. Air permeability coefficient / cm2.s -1 .pa -1 is 6.81×10 -14 ;
[0065] 200℃, 72h test of its thermal oxidation aging properties: hardness change 0, tensile strength change rate -3.1%, elongation at break change rate -9.87%, high temperature permanent compression deformation 41.4%;
[0066] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 0%, the Shore hardness change is -2, and the volume change rate is +0.23%;
[0067] Example 4
[0068] Step 1) activating 7.5 kg of fluororubber reclaimed rubber powder (200 mesh) at 200° C. for 40 min;
[0069] Step 2) 25 kg of fluororubber raw rubber is plasticized at room temperature for 5 minutes to obtain plasticized rubber, and then the activated 200-mesh fine fluororubber recycled rubber powder, 7.5 kg of clay and 2.25 kg of powdered 100-mesh polytetrafluoroethylene are evenly dispersed in an internal mixer to obtain a mixture, and the mixture is added to the plasticized rubber at 160±5°C and mixed evenly to obtain mixed plastic, with the mixing time being 15 minutes; then a bisphenol vulcanization system (0.5 kg of bisphenol AF, 0.125 kg of BPP), 1.5 kg of calcium hydroxide, 0.75 kg of magnesium oxide, and 0.75 kg of ferric oxide are added and dispersed evenly.
[0070] Step 3) Add the synthesized plastic mixture into a twin-screw extruder at 190° C., and perform continuous crosslinking reaction by means of dynamic vulcanization blending and strong mechanical shear stress, and the crosslinking time is 40 minutes.
[0071] Step 4) The above material is molded into a sheet at 190° C. for 40 minutes, and a secondary cross-linking reaction is carried out at 220° C. for 8 hours to obtain a high-quality thermoplastic elastomer sealing material.
[0072] Performance testing of the product: Performance testing was carried out according to JF01-58-2019. The prepared special sealing material has a Mooney viscosity of 55 (ML1+10, 121°C), low-temperature brittleness of -22°C, tensile strength of 12MPa, elongation at break of 284%, Shore hardness of 86, compression permanent deformation of 2.8%, and air permeability coefficient / cm2.s -1 .pa -1 5.64×10 -14 ;
[0073] 200℃, 72h test of its thermal oxidation aging properties: hardness change 0, tensile strength change rate -1.6%, elongation at break change rate -0.4%, high temperature permanent compression deformation 34.4%;
[0074] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 0%, the Shore hardness change is -2, and the volume change rate is +0.05%.
[0075] Example 5
[0076] Step 1) activating 3 kg of fluororubber reclaimed rubber powder (200 mesh) at 200° C. for 30 min;
[0077] Step 2) 30 kg of silicone rubber raw rubber was plasticized for 10 min at room temperature to obtain plasticized rubber, and then the activated 200-mesh fine fluororubber recycled rubber powder, 6 kg of clay and 0.9 kg of powdered 100-mesh polytetrafluoroethylene were evenly dispersed in an internal mixer to obtain a mixture, and the mixture was added to the plasticized rubber at 160±5°C and mixed evenly to obtain mixed plastic, and the mixing time was 15 min; then a peroxide vulcanization system (0.6 kg DCP, 0.15 kg DM), 0.9 kg magnesium oxide, 2.7 kg ferric oxide, and 2.1 kg hydroxy silicone oil were added and dispersed evenly.
[0078] Step 3) Add the synthesized plastic mixture into a twin-screw extruder at 180° C., and perform continuous crosslinking reaction by means of dynamic vulcanization blending and strong mechanical shear stress, and the crosslinking time is 30 minutes.
[0079] Step 4) The above material is molded into a sheet at 180° C. for 20 minutes, and a secondary cross-linking reaction is carried out at 200° C. for 8 hours to obtain a high-quality thermoplastic elastomer sealing material.
[0080] Performance testing of the product: According to JF01-58-2019, the performance test of the prepared special sealing material is 35 (ML1+10, 121°C), low-temperature brittleness is -73°C, tensile strength is 8.9MPa, elongation at break is 269.2%, Shore hardness is 76, compression permanent deformation is 6.14%, air permeability coefficient / cm2.s -1 .pa -1 4.27×10 -14 ;
[0081] 200℃, 72h test of its thermal oxidation aging properties: hardness change -1, tensile strength change rate -3.9%, elongation at break change rate -8.28%, high temperature permanent compression deformation 51.21%;
[0082] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 0.3%, the Shore hardness changes by -5, and the volume change rate is +0.76%.
[0083] Comparative Example 1
[0084] No recycled rubber powder was added, and the rest of the formulation and process parameters were consistent with those in Example 5.
[0085] Performance testing of the product: According to JF01-58-2019, the prepared special sealing material has a Mooney viscosity of 34 (ML1+10, 121°C), low-temperature brittleness of -74°C, tensile strength of 8.3MPa, elongation at break of 246.6%, Shore hardness of 72, compression permanent deformation of 6.36%, and air permeability coefficient / cm 2 .s -1 .pa -1 4.4×10 -14 ;
[0086] 200℃, 72h test of its thermal oxidation aging properties: hardness change 0, tensile strength change rate -5.18%, elongation at break change rate -10.5%, high temperature permanent compression deformation 51.69%;
[0087] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 3%, the Shore hardness changes by -6, and the volume change rate is +0.88%.
[0088] Table 1 Test results of special sealing materials
[0089]
[0090] As shown in Table 1, the Mooney viscosity of the RPTPE prepared by the present invention is 35-59 (ML1+10, 121°C), the low temperature brittleness is -18--73°C (relative to the type of raw rubber), the tensile strength is 8.9-12MPa, the elongation at break is 268.6%-292%, the Shore hardness is 76-86, the physical properties of compression permanent deformation are 2.8-13.8%, and the air permeability coefficient / cm2.s-1.pa-1 is 4.27×10-14-7.13×10-14;
[0091] 200℃, 72h test of its thermal oxidation aging properties: hardness change -1~0, tensile strength change rate -3.9~-1.5%, elongation at break change rate -9.87~-0.4%, high temperature permanent compression deformation 34.4~51.21%;
[0092] After soaking in ASTM 3# oil for 70 hours, wipe it dry and let it stand for 0.5 hours to test its oil resistance. The mass change rate before and after oil resistance is 0-0.3%, the Shore hardness changes from -5 to -2, and the volume change rate is +0.02% to +0.76%;
[0093] The product performance meets the requirements of "Technical Conditions for O-Ring Rubber Sealing Rings for Air Conditioning Systems (HFC-134a) JF01-58-2019". Compared with DuPont's fluorosilicone material LS5043H, the tensile strength, oil resistance and aging resistance are significantly improved, while the cost is reduced by 20% to 30%.
[0094] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. An environmentally friendly corrosion-resistant thermoplastic elastomer sealing material, characterized in that: Made from the following raw materials in parts by weight: 1 to 6 pieces of plastic; 50-65 parts of raw rubber; 5-30 parts of recycled rubber powder; 1 to 6 parts of acid absorbent; 6-20 parts of filler; Vulcanization system ingredients: 1-3 parts of vulcanizing agent, 0.2-1.5 parts of accelerator; 1 to 6 parts of antioxidant; Other additives 0-5 parts.
2. The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 1, characterized in that: The plastic is polytetrafluoroethylene particles with a mesh size of 120 to 200.
3. The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 1, characterized in that: The raw rubber is special rubber.
4. The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 1, characterized in that: The regenerated rubber powder is special rubber waste rubber powder or special rubber regenerated rubber powder, and the mesh number is ≥100 meshes.
5. The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 1, characterized in that: The acid absorbent is one or more of magnesium oxide, calcium hydroxide, zinc oxide and calcium carbonate.
6. The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 1, characterized in that: The vulcanization system is one of a bisphenol vulcanization system, a peroxide vulcanization system or an amine vulcanization system.
7. The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 1, characterized in that: The filler is a mineral material.
8. The environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 1, characterized in that: The antioxidant is ferric oxide.
9. A method for preparing the environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1) Activating the regenerated rubber powder at high temperature, the activation temperature is 200° C., and the activation time is 30 to 50 minutes; Step 2) The raw rubber is plasticized at room temperature for 5 to 10 minutes to obtain plasticized rubber, and then the activated recycled rubber powder, filler, plastic and plasticized rubber are mixed and kneaded evenly in a kneader or an internal mixer at 160±5°C to obtain mixed plastic, and the mixing time is 10 to 15 minutes; then a vulcanization system compounding agent, an acid absorber, an antioxidant and other additives are added to disperse them evenly; Step 3) placing the synthesized plastic into a twin-screw extruder at 180-200° C., and performing continuous crosslinking reaction by means of dynamic vulcanization blending and strong mechanical shear stress, with a crosslinking time of 20-40 minutes; Step 4) performing a secondary cross-linking reaction at 200-220° C. for 6-8 hours.
10. The method for preparing the environmentally friendly corrosion-resistant thermoplastic elastomer sealing material according to claim 9, characterized in that: Before the secondary cross-linking reaction, the material obtained by the primary cross-linking reaction is molded at 180-200° C. for 20-40 minutes to form a sheet.